KARAKTERISTIK KEBAHASAAN TOKOH LAKI-LAKI DAN PEREMPUAN PADA FILM “TEKA-TEKI TIKA” KARYA ERNEST PRAKASA - Rupidara, Indar; Apriyani, Tristanti (Universitas Ahmad Dahlan, 2023)
This research focuses on the language features of the male and female characters in the film “Teka Teki Tika” by Ernest Prakasa. The author presents a characteristic description of the language of male and female characters in films based on Lakoff's theory. In this study, the authors used a qualitative descriptive method with careful observation techniques in obtaining data. The purpose of this study is to describe and identify the language features of the male and female characters in the film